84‐2: Invited Paper: High‐Resolution Additive Manufacturing in the Fabrication of Micro‐LED Displays - Granek, Filip; Grądzka-Kurzaj, Iwona; Gadzalińska, Jolanta; Witczak, Łukasz; Fiączyk, Karolina; Kowalczewski, Piotr (SID International Symposium Digest of technical papers, 2024)
This paper demonstrates the use of Ultra‐Precise Dispensing, a high‐resolution additive manufacturing method, in the fabrication of Micro‐LED displays. We demonstrate advancements in achieving ultra‐small feature sizes, high aspect ratios, and the ability to print on complex substrates. The paper presents a number of use cases, such as interconnections on complex topographies, edge printing, microvias filling, and microbumps dispensing. It summarizes the relevance of this technology for Micro‐LED displays fabrication and discusses the prospective future developments in the field of additive manufacturing for display fabrication.